ЎЗБЕК ВА ОЗАРБАЙЖОН ХАЛҚЛАРИНИНГ АДАБИЁТ СОҲАСИДАГИ АЛОҚАЛАРИ РИВОЖИДА МАҚСУД ШАЙХЗОДАНИНГ ЎРНИ - Адилов, Ф.А. (SCIENCE and SOCIETY, 2021)
This article deals with the development of relations between Uzbekistan and Azerbaijan in the field of literature, the life, work, created immortal works and the activities of Maqsud Sheikhzoda, the favorite poet of the two peoples, a great playwright, literary critic and translator in Uzbekistan.
Keywords: literature; people; scientific relations; Internasional; Homeland; journalism; relations; epic; playwright; oral creativity of the people